Pengaruh Disiplin Kerja Dan Komunikasi Terhadap Kinerja Pegawai Kantor Kecamatan Beji Kota Depok - Imam Dawamuz Zikri; Asep Sulaeman (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to determine the effect of work discipline on employee performance, to determine the effect of communication on employee performance, to determine the effect of work discipline and communication simultaneously on employee performance. The method used is associative quantitative. The population used was 91 respondents, the sampling technique used was saturated using a sample of 91 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple linear regression correlation analysis. The results of this research are a correlation coefficient of 0.783, meaning that the two variables have a strong level of influence or relationship on the employee performance variable (Y) with a coefficient of determination of 61.3%. With the results of this research, work discipline has a sig of 0.000 < 0.05, so Ho is rejected. Ha which means that work discipline has a significant and influential effect on employee performance. communication has a sig of 0.000 > 0.05, then Ho is accepted and Ha is rejected, which means that communication has no effect and is not significant on employee performance. F count 69.696 > 3.10 and sig 0.000 < 0.05 then Ho is rejected and Ha is accepted then Ho is rejected Ha is accepted which means that work discipline and communication have a simultaneous and significant effect on employee performance. Effective work discipline and conducive communication will improve employee performance